Embryogenesis in Oak species. A review - Gomez-Garay, Aranzazu; Manzanera, Jose A.; Pintos-Lopez, Beatriz (Forest Systems, 2014)
Aim of study: A review on the propagation methods of four Quercus species, namely Q. suber, Q. robur, Q. ilex and Q. canariensis, through somatic embryogenesis and anther embryogenesis are presented. Area of study: The study comprises both Mediterranean and Atlantic oak species located in Spain. Material and Methods: Somatic embryogenesis was induced on immature zygotic embryos of diverse oak species, permitting the multiplication of half-sib families. Induction of haploid embryos and doubled haploids was assayed in both Q. suber and Q. ilex by temperature stress treatments of anthers containing late vacuolated microspores. The haploid origin of the anther embryos has been evaluated by quantitative nuclear DNA analysis through flow cytometry and by DNA microsatellite markers. Genetic transformation of cork oak has also been performed by means of Agrobacterium tumefaciens vectors. Proteomic analysis has been conducted to screen the diverse protein profiles followed by in vitro derived embryos during their development. Research highlights: Successful plant regeneration from both somatic and haploid embryos has been achieved. In the particular case of cork oak, doubled-haploid plants were obtained. Plantlets regenerated from selected parent trees through somatic embryogenesis were acclimated in the greenhouse and in the nursery, and were planted in an experimental plot in the field. Preliminary evaluation of the cork quality of the plants showed a good heritability correlation with the parent trees. This article revises the work of and is dedicated to Dr. M.A. Bueno, who devoted much of her professional life to the research on Biotechnology and Genetics of forest species, leading the Laboratory of Forest Biotechnology at the Spanish Institute of Agronomic Research (INIA). Key words: anther embryogenesis; microspore; pollen; Quercus canariensis; Quercus ilex; Quercus robur; Quercus suber; somatic embryogenesis.